Characterization of a carboxyterminal peptide fragment of the human choriogonadotropin beta-subunit excreted in the urine of a woman with choriocarcinoma. - Amr, S (1983)
We have observed low-molecular weight carboxyterminal fragments of the human choriogonadotropin (hCG) beta-subunit in the urines of several women with choriocarcinoma, and we have characterized one fragment in detail. Its apparent molecular weight by gel chromatography on Sephadex G-100 was 14,200. The fragment was not adsorbed to concanavalin A-Sepharose, indicating that it lacked the asparagine-linked carbohydrate groups of intact hCG beta. It was active in radioimmunoassays (RIA) using antisera either to the hCG beta carboxyterminal peptide (CTP) or to the desialylated hCG beta CTP (hCG beta as-CTP), indicating the presence of not only the hCG beta carboxyterminus but also desialylated O-serine-linked carbohydrate side chains on the fragment. It lacked luteinizing hormone/choriogonadotropin radioreceptor activity and hCG beta conformational immunoreactivity (SB6 RIA). On Sephadex G-100 gel chromatography, the elution profiles of this fragment and the hCG beta as-CTP(115-145) prepared by trypsin digestion of as-hCG were essentially indistinguishable (apparent molecular weights 14,200 and 14,000, respectively). The immunological characteristics of the fragment in both hCG beta CTP and hCG beta as-CTP RIA were indistinguishable from those of the hCG beta as-CTP(115-145) glycopeptide. Carboxyterminal fragments of hCG beta were evident in urine specimens obtained from 10 of 11 patients with choriocarcinoma but not in those obtained from normal subjects who were given an intravenous infusion of highly purified hCG. Of six pregnant women, only the one at term excreted carboxyterminal fragments of hCG beta and then only in trace amounts. We conclude that hCG beta carboxyterminal fragments, including one that is indistinguishable from the tryptic glycopeptide hCG beta as-CTP(115-145), can occur naturally in the urine of patients with choriocarcinoma.